Konsep Thaghut dalam Alqur’an : (Analisis Kritis Tafsir Sayyid Qutb, Fii Zhilal Al-Quran) - Marzuqi, Ammar Zain; Azizah, Alfiyatul (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
The thoughts and understanding of Indonesian society about thaghut are very diverse, sometimes some groups interpret it excessively so that it becomes an extreme movement. The author takes the theme of the concept of thaghut from the perspective of Sayyid Qutb's interpretation, because some people understand Sayyid Qutb's interpretation is an interpretation that contains radical and extreme elements, so many say Sayyid Qutb's interpretation as a reference to modern khowarij groups (extremists). The purpose of this study the author wants to examine how the interpretation of Sayyid Qutb actually in the problem of thaghut. This research uses the method of library reaserch or library research using Sayyid Qutb's tafsir analysis, which is then concluded objectively. As for the results of this study, the meaning of thaghut according to Sayyid Qutb which is a manhaj, order system that is not based on the rules of Allah, or laws, regulations, traditions that are not in accordance with the shari'a of Allah. Then in his interpretation of Surah Al Maidah 44, 45 and 47 whoever rules with other than Allah's law (thaghut) is pinned to the culprit of the nature of kufr, wicked and unjust, as a consequence of followers of thaghut. With that can make some groups misunderstand, so that it becomes an extreme movement if without seeing his interpretation as a whole, especially about religious moderation in Surah Al Baqarah 143 to maintain community harmony.